Clinicolaboratory profile and outcome of dengue fever cases in peak season of an academic year among pediatric population admitted to teaching hospital, Bangalore, Karnataka, India - Varghese, Deepthy Alice; C., Shivaprakash Sosale; ., Keshavmurthy; P., Anusha P.; Reddy, Chikkanarasa (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue is a vector borne diseases with varied clinical manifestations, a major concern to public health globally. This study was done to describe the salient clinical as well as haematological profile of serologically confirmed cases of dengue fever and outcome in admitted cases. Methods: This was a prospective study conducted at major Government teaching Hospitals in Bangalore from July 2019 to December 2019. Total 164 cases of dengue fever were enrolled and classified as per WHO guidelines. The clinical profile and demographic profile was recorded in a structured questionnaire format. Haematological parameters on admission, duration of stay and outcomes were analysed. The outcomes of the cases were mentioned as improved and death. Results: In this study commonly affected age band was adolescents group (36.6%) without any sex predilection. Maximum number of dengue cases were presented with warning signs (87.5%), 14 (8.69%) cases without warning signs and 6 (3.72%) with severe dengue. Fever was the most common symptom (100%), followed by vomiting (58%) and abdominal pain (38.5%). NS1 antigen positive cases (61.5%). Severe Leukopenia was present in 57% of cases and Thrombocytopenia in all admitted patients (100%). Most of the cases were treated with antipyretics, oral fluids (46%) and IV fluids (53%), only single case received platelet transfusion. Duration of stay was more in severe dengue cases. Mortality of our study was 1.8%. Conclusions: Dengue presents with varied clinical features. Community awareness, early diagnosis and management and vector control measures needs to be strengthened in order to reduce the increasing number of dengue case. Both clinical, haematological parameters should be monitored for better outcome.